Sprachenwahl? Mehrsprachige Interaktion in internationalen Arbeitsgruppen im hochschulischen Kontext - Tork, Silke (Glottodidactica, 2025)
Based on two datasets (collected at a national university in Germany and an international university in Italy), this study focuses on negotiating processes for language choice in multilingual working groups, in which German is both a first and second language, or a foreign language for individual participants. In the task-oriented group work, English and German materials are used and the participants bring a variety of linguistic backgrounds. The negotiation sequences are analysed using the methods of multimodal interaction analysis with the focus on multilingual competencies. Thus, the emphasis is less on individual language skills in a specific language, e.g. in German as a foreign or second language, but more so on hitherto underrepresented multilingual competencies. Such competencies go beyond the distinction of named languages and include the integration and connection of various resources. This integrated view of the speakers’ linguistic repertoires and their varied multilingual competences is gaining importance in increasingly pluralistic societies.